The human person: anthropological foundation of human rights - Boluarte Drago, Analyda (2019)
This paper highlights the humanistic aspect of human rights within a globalized world, and particularly in government policies, which has neglected the importance of human rights in overcoming many conflicting aspects of our society. In this perspective it becomes clear the condition of human nature, from its ontological root, which gave rise to and foundation for Universal Human Rights, leaving certain relativistic, subjectivist and even reductionist approaches that do not respond to the vision integral of the person.